1995
DOI: 10.1007/bf02510505
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of ajoene and the microwave power density memories of water on germination inhibition of fungal spores

Abstract: The synergistic effects of ajoene and the microwave power density memories of water on germination inhibition of some fungal spores are examined. The study reveals power memory varying different synergistic effects of different concentrations of ajoene on the inhibition of spore germination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Despite several reports suggesting that the improvement in the digestion process after microwave pretreatment is mainly attributable to the heating effect of microwaves, recent studies have shown that may not necessarily be the case (Coelho et al, 2011, Shazman et al, 2007. Changes in physiological characteristics of microorganisms after exposure to microwaves (Rai et al, 1995;Singh et al, 1994), increases in the inactivation rate of microorganisms in comparison with conventionally treated samples (Dreyfuss and Chipley, 1980;Hong et al, 2004), and increases in microbial biological activity such as biogas production or growth rate (Banik et al, 2006;Grundler et al, 1992;Grundler and Keilmann, 1983), were reported as examples of non-heat-related effects. These phenomena are frequently justified by the existence of an athermal effect, because they occur independently of temperature rise in media irradiated with microwaves.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several reports suggesting that the improvement in the digestion process after microwave pretreatment is mainly attributable to the heating effect of microwaves, recent studies have shown that may not necessarily be the case (Coelho et al, 2011, Shazman et al, 2007. Changes in physiological characteristics of microorganisms after exposure to microwaves (Rai et al, 1995;Singh et al, 1994), increases in the inactivation rate of microorganisms in comparison with conventionally treated samples (Dreyfuss and Chipley, 1980;Hong et al, 2004), and increases in microbial biological activity such as biogas production or growth rate (Banik et al, 2006;Grundler et al, 1992;Grundler and Keilmann, 1983), were reported as examples of non-heat-related effects. These phenomena are frequently justified by the existence of an athermal effect, because they occur independently of temperature rise in media irradiated with microwaves.…”
Section: Introductionmentioning
confidence: 99%